Sun warrior - Cast, P. C. (Cast, P. C. Tales of a new world, 2017)
"The battle lines have been drawn and Mari, an Earth Walker and Nik, a Companion, who were once from rival clans, now find themselves fighting to save each other and their people from destruction"--Jacket.